FreeHyTE: a hybrid-Trefftz finite element platform. (July 2018) - Moldovan, Ionuţ Dragoş; Cismaşiu, Ildi
Highlights: FreeHyTE is the first public, open-source and user-friendly computational platform using hybrid-Trefftz finite elements. FreeHyTE is easy to use and amenable to expansion. FreeHyTE features pre-programmed procedures for all phases of the computation. The same finite element procedure is used for elliptic, parabolic and hyperbolic problems. Abstract: FreeHyTE is a public, open-source and user-friendly software for the solution of initial boundary value problems using hybrid-Trefftz finite elements. FreeHyTE is designed to be straightforward to use, even by analysts unacquainted to the Trefftz elements, and amenable to expansion by researchers willing to test their new ideas without having to code common procedures from scratch. To support users, FreeHyTE features intuitive graphical interfaces, automatic mesh generators and adaptive p -refinement procedures. To support developers, FreeHyTE approaches Trefftz elements through a unifying perspective, applicable to hyperbolic, parabolic and elliptic boundary value problems alike. It provides standardized procedures in all phases of the algorithm, including data input, construction and manipulation of the solving system, and post-processing of the results. Moreover, the modular structure of FreeHyTE enables the integration of existing procedures into new modules with minimal coding effort. FreeHyTE's distribution is free under the terms of the GNU General Public License and supported by theory, installation, user's and developer's manuals to quickly get new users and developers started.